(3TQM OjhGf GdeJfHis - (3CHi GdbGSe EHQGgje Hf RcQjG GHf GdEadjdi GdbQWHis; (3GdeJfHj , CHh GdWjH,J (B354 (3g` s
(3ChdgG (B:s
(3cFjHG JhbGfi GdYhGRd ai Gdghi ceG jJhbi QjV GdNjd MGReg s
(3BNQgG (B:s
(3aEPG eG GTJgi NdhOc OGY bGd (B: (3dG RdJ Ch JQi dc eKdG s
(3fSNI KGfjI JJab ai CNQgG eY GdfSNI GdChdi HGNJdGa ai HYV GdCdaGXs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B115 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B201s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B146 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B811s
Keywords: (3GdCOHs